Real-time monitoring and control of water pump system / Febry Yadi Zainal - Febry Yadi, Zainal (2017)
Common machine is used in industries to transfer liquid is a centrifugal pump that uses an induction motor as a driver. The unexpected error of the machine is the main cause of loss due to cessation of production, and extra cost will be needed for repair and replacement of damaged parts. Therefore, required a system that can monitor and control the machine to know the conditions and avoid the damage of the system. Hence, the objective of this work includes design and development of SCADA based remote control and real-time monitoring of water-pump systems, it is composed of two parts, the first part is motor control and the second part is monitoring systems that implement the IEC 60870-5-101 standard protocol. This work presents the design and development of water pump monitoring system that uses 3-phase induction motor. Inverter and motor control are designed to run and control the speed of the motor and communicate with the SCADA system. SCADA system is used as monitoring system and process control of fault detection and isolation (FID). The proposed motors control for 3 phase induction motors used space vector pulse width modulation strategy (SVPWM). The v/f strategy (Volt/Hz Control) is used to control the induction motor speed because of its simplicity. The motor control unit drives the motor via an inverter switched by DSP (TMS320F2812). On monitoring side, SCADA has three main parts, namely a remote terminal unit (RTU), the master system, and communication system. RTU collects all the data and make the execution of a command, the master of the proposed system is a software application GUI for water pumping systems according to IEC 60870-5-101 via visual basic.net are low-cost and user-friendly, and the communication system used is the RS232 and RS422 serial communication with the IEC 101 standard protocol.In this work, the implementation of SCADA system in remote and water-pump monitoring system based on IEC 6870-5-101 has been implemented. The average error between oscilloscope measurement and SCADA system was found to be 1.81%. It can be concluded that the SCADA system with IEC 60870-5-101 standard protocol could be implemented on real time monitoring and remote control of water-pump systems.